2022
DOI: 10.3390/cancers14102552
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporters 1 and 4 and Prognosis in Small Bowel Neuroendocrine Tumors

Abstract: Monocarboxylate transporters (MCTs) are cell membrane proteins transporting lactate, pyruvate, and ketone bodies across the plasma membrane. The prognostic role of MCTs in neuroendocrine tumors is unknown. We aimed to analyze MCT1 and MCT4 expression in small bowel neuroendocrine tumors (SB-NETs). The cohort included 109 SB-NETs and 61 SB-NET lymph node metastases from two Finnish hospitals. Tumor samples were immunohistochemically stained with MCT1 and MCT4 monoclonal antibodies. The staining intensity, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Patient ages ranged between 18 to 98 years, and all samples were collected from adult patients (considering the studies where information on age was available). MCT1 expression was assessed in different cancers: one study in melanoma [ 41 ], oral cavity tumours [ 42 ], endometrial cancer [ 43 ], testicular germ cell tumours [ 44 ], soft tissue sarcoma [ 45 ], head and neck cancer [ 46 ], pancreatic ductal adenocarcinoma (PDAC) [ 47 ], small bowel neuroendocrine tumours [ 48 ], synovial sarcoma [ 49 ], adrenocortical carcinoma [ 50 ], small cell lung cancer (SCLC) [ 35 ], gastrointestinal stromal tumours (GIST) [ 51 ], osteosarcoma [ 30 ], malignant pleural mesothelioma [ 52 ], Hodgkin lymphoma [ 53 ], oropharyngeal squamous cell carcinoma (OSCC) [ 54 ] and cancer of unknown primary origin [ 55 ]; two studies in prostate adenocarcinoma [ 56 , 57 ], colorectal cancer (CRC) [ 58 , 59 ], clear cell renal cell carcinoma (RCC) [ 60 , 61 ], esophageal squamous cell carcinoma (ESCC) [ 62 , 63 ], non-Hodgkin lymphoma (NHL) [ 64 , 65 ] and gastric cancer [ 66 , 67 ]; three studies in non-small cell lung cancer (NSCLC) [ 68 , 69 , 70 ] and breast cancer [ 71 , 72 , 73 ]; and four studies in bladder cancer [ 27 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient ages ranged between 18 to 98 years, and all samples were collected from adult patients (considering the studies where information on age was available). MCT1 expression was assessed in different cancers: one study in melanoma [ 41 ], oral cavity tumours [ 42 ], endometrial cancer [ 43 ], testicular germ cell tumours [ 44 ], soft tissue sarcoma [ 45 ], head and neck cancer [ 46 ], pancreatic ductal adenocarcinoma (PDAC) [ 47 ], small bowel neuroendocrine tumours [ 48 ], synovial sarcoma [ 49 ], adrenocortical carcinoma [ 50 ], small cell lung cancer (SCLC) [ 35 ], gastrointestinal stromal tumours (GIST) [ 51 ], osteosarcoma [ 30 ], malignant pleural mesothelioma [ 52 ], Hodgkin lymphoma [ 53 ], oropharyngeal squamous cell carcinoma (OSCC) [ 54 ] and cancer of unknown primary origin [ 55 ]; two studies in prostate adenocarcinoma [ 56 , 57 ], colorectal cancer (CRC) [ 58 , 59 ], clear cell renal cell carcinoma (RCC) [ 60 , 61 ], esophageal squamous cell carcinoma (ESCC) [ 62 , 63 ], non-Hodgkin lymphoma (NHL) [ 64 , 65 ] and gastric cancer [ 66 , 67 ]; three studies in non-small cell lung cancer (NSCLC) [ 68 , 69 , 70 ] and breast cancer [ 71 , 72 , 73 ]; and four studies in bladder cancer [ 27 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies did not mention positive or negative controls [ 30 , 35 , 47 , 49 , 51 , 52 , 53 , 55 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Two and six studies (respectively) reported the use of negative [ 43 , 46 ] or positive [ 42 , 44 , 48 , 54 , 60 , 66 ] controls, and eight studies reported using both negative and positive controls [ 27 , 41 , 45 , 50 , 57 , 59 , 63 , 65 ]. For negative controls, replacement or abolishment of primary antibodies were the most reported methods; for positive controls, the most used samples were colon and colorectal carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations